TRANSFORMATIVE BUSINESS GROWTH STAGE MODEL TO FACE UNCERTAINTY - Bachtiar, Nia Kurniati; Waharini, Faqiatul Mariya; Yuliani, Nur Laila; Tai, Do Anh; Hanh, Pham Van (Jurnal Manajemen dan Kewirausahaan, 2024)
The business landscape was characterized by rapid change, intense competition, and various substitute products. These factors shortened business life cycles and hindered business growth. Therefore, there was a need for a more appropriate model that could suit the current condition. The study aimed to develop a transformative Growth Stage Model (GSM) effectively adapted to modern challenges and uncertainty. This qualitative approach involved inductive theory building with seven case studies of SME owners in Yogjakarta and Central Java. Developed models, patterns, and interview themes were built, including resilience, business performance, and leadership for the early growth, growth, and decline stages. In addition, these patterns and themes were used to develop three stages of transformative GSM known as GSM 4.0.